Regio- and Stereoselective Addition of Brønsted Acids to Yndiamides: Synthesis of N,O,N- and N,S,N-Trisubstituted Ketene Acetals - Garry, Olivia L.; Mansfield, Steven J.; Anderson, Edward A. (Synthesis, 2021)
Yndiamides, N,N-disubstituted alkynes, are versatile building blocks for the synthesis of nitrogen-containing organic molecules. Unlike ynamides, relatives that are inherently polarized by a single nitrogen substituent, their pseudo-symmetric nature renders regioselective reactions challenging. Here we report investigations into the regioselective addition of Brønsted acids to non-symmetric yndiamides, a reaction that delivers N,O,N- and N,S,N-trisubstituted ketene acetals with excellent regio- and stereoselectivity.
Keywords: yndiamides; keteniminium ions; hydroalkoxylation; regioselectivity